Enhancement of Tumor Contrast on Radioimmunoscans by Using Mixtures of Monoclonal Antibody F(ab’)2 Fragments - Munz, D. L.; Alavi, A.; Koprowski, H.; Herlyn, D. (Nuklearmedizin - NuclearMedicine, 1986)
F(ab’)2 fragments of MAbs GA 73-3 (IgG 2a) and CO 29.11 (IgG 1), which detect distinct antigenic determinants on adenocarcinoma cells of the gastrointestinal tract, were labeled with 131I using the iodogen method. 41 nude mice bearing SW-948 CRC tumors were injected either with a mixture of 100 ¼Ci (11 ¼g) each (n = 9) of the two 131l-F(ab’)2 fragments or with either fragment alone at various doses (each group consisting of 8 mice): GA 73-3,100 ¼Ci (11 ¼g) and 200 ¼Ci (25 ¼g); CO 29.11,100 ¼Ci (11 ¼g) and 200 ¼Ci (26 ¼g). Whole-body images of the mice were obtained daily for up to six days after injection. Ratios of cpm/pixel in the tumor to those in the rest of the body (rob), representing tumor contrast, were significantly (p <0.05) higher in the group of mice injected with the mixture (3.9 ± 1.5) as compared to those given 100 or 200 jiCi of either fragment separately. The biological half-life (T1/2 biol) of the mixture (44.7 ± 14.5 h) in the CRC tumors was significantly (p <0.05) longer than T1/2 biol determined in the groups given either fragment alone. Tv bioL in the rob was similar in all groups of mice examined.F(ab’)2-Fragmente der monoklonalen Antikörper (MAbs) GA 73-3 (IgG 2a) und CO 29.11 (IgG 1), welche verschiedene, gut charakterisierte Antigendeterminanten auf Adenokarzinomzellen des Gastrointestinaltraktes erkennen, wurden mit Hilfe der Iodogen-Methode mit 131 J markiert. 41 kolorektale Karzinome (CRC) menschlichen Ursprungs tragenden Nacktmäusen wurde entweder eine Mischung von jeweils 100 ¼Ci bzw. 11 ¼g (n = 9) der beiden 131J-markierten F(ab’)2-Fragmente oder jedes markierte Fragment separat in verschiedener Dosierung verabfolgt (jede Gruppe bestand aus 8 Mäusen): G A 73-3: 100 ¼Ci (11 ¼g) und 200 ¼Ci (25 ¼g); CO 29.11: 100 ¼Ci (11 ¼g) und 200 [id (26 ¼g). Ganzkörperszintigramme der Tiere wurden bis zu sechs Tagen nach Injektion angefertigt. Die Verhältnisse der cpm/pixel in den Tumoren zu denjenigen im Restkörper (rob), welche den Tumorkontrast wiedergeben, waren in der Gruppe mit dem Antikörper-Fragment-Gemisch (3,9 ± 1,5) signifikant (p <0,05) höher als in jenen Gruppen von Mäusen, die lediglich jeweils eine Komponente in verschiedener Dosierung erhalten hatten. Die biologische Halbwertszeit (T1/2 biol) des MAb-Fragment- Gemisches in den CRC-Tumoren (44,7 ± 14,5 h) war signifikant (p <0,05) länger als die in den Gruppen mit nur jeweils einem applizierten Fragment ermittelte. T1/2 biol. im r°b der Mäuse war in allen untersuchten Gruppen ähnlich.